Temporal geospatial assessment of cocoa pollinator, Forcipomyia in cocoa plantation area - Saripah Bakar,; Nor Aizam Adnan,; Ummu Syaira Ain Redzuwan, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2019)
The objective of the study is to investigate the pollinator, Forcipomyia spp. (Diptera: Ceratopogonidae) population after augmentation of different breeding medium stuffed in the portable breeding container. The observation was carried out both in the laboratory and in the cocoa field, and temporal geospatial assessment was obtained through geospatial analysis. A spatial distribution map of the pollinator population was produced to determine the distribution according to substrates, distances, and duration. The population of the cocoa pollinator in the laboratory was observed for 60 days. Meanwhile, field observation was carried out for the period of 94 days (Days 1, 12, 24, 38, 52, 66, 80 and 94), at four distances (2, 5, 8 and 12 m). Three breeding mediums were selected, which were cocoa pod husk, banana stump, and combination of cocoa pod husk and insect-infested pods. The data were analyzed using statistical software, as well as using Geographical Information System (GIS), and geospatial statistic. Contradict results were obtained both for laboratory and in the field where banana stumps harbored the highest number of pollinators in the former observation. Meanwhile, in the latter observation, cocoa pod husk harbored a higher number of captured pollinators compared with the other breeding medium. The results denoted that cocoa pod husk and banana stumps should be considered as the most appropriate medium for pollinator increment in the cocoa plantation. Continue adding the breeding medium inside the container after Day-60 and increased the number of an individual breeding container are promoted for the sustainability of the population for more extended period. With the aid of geospatial interpolation technique, temporal geospatial assessment of cocoa pollinator can be determined more accurately. This information will be benefited cocoa operators to determine the best time to augment more breeding medium as well placement of breeding substrates to increased pollinator population in the cocoa field.